Paulo e a escravidão: uma análise do posicionamento de Paulo frente à escravidão com enfoque na Carta a Filêmon - Gomes, Israel Mazzacorati (2012)
This research analyzes the attitude of the Apostle Paul against the institution of slavery in the Roman Empire in the New Testament period. Explains slavery as a form of domination that posed a conflict to be overcome by the Pauline communities. Shows that Paul's theological thinking was forged through conflict experienced throughout his career as a missionary, pastor and theologian. Sets out the main themes of Pauline theology regarding the issue of slavery and freedom. To this end, part of the conversion experience of the apostle, namely, the encounter with the risen Christ, highlighting the importance of this event and theological implications of it. Take the title of Kyrios as one of the main hermeneutic for understanding the attitude of Paul in the face of situations of domination in society. Examines Paul's letter to Philemon as a result of a historical process in which Paul finds himself compelled to place himself before the institution of slavery and how this position can be found in his theology. Proposes a sense to update letter to Philemon, demonstrating the applicability of the principles used by Paul, especially as regards agape.